(untitled) (Journal of Life and Earth Science, 2014)
The present study was designed to investigate the morphology of reproductive system and egg anatomy of the domestic hen (Gallus domesticus L.). The system consists of oviduct and ovary. The oviduct consists of infundibulum, magnum, isthmus, uterus and vagina which are sole distributor for making nutrition enriched egg. The anatomy of egg revealed that there are calcareous eggshell, shell membranes, egg white, vitelline membrane, egg yolk, and germinal disc. The fertilized egg showed a concentric circle around the nucleus known as blastoderm that contained area pellucida and area opaca whereas an unfertilized egg showed nucleus as white spot (blastodisc). Primordial germ cells (PGCs) are progenitor cells of ova and spermatozoa and they originate from the epiblast of the central part of the area pellucida. The microscopic structure of eggshell rendered leathery cuticle, fibrous matrix and shell membranes. The egg protects itself by its own mechanism from being injured and provides a complete diet for the developing embryo. DOI: http://dx.doi.org/10.3329/jles.v8i0.20133 J. Life Earth Sci., Vol. 8: 1-10, 2013